The Role of the Regional Disaster Management Agency (BPBD) in Tackling Natural Disasters (Manado City) - Mursid Pangalima; Dian Ferriswara; Ulul Albab (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes the role of the Manado City Regional Disaster Management Agency (BPBD) in managing natural disasters and examines the challenges faced, along with efforts to overcome them. A qualitative descriptive approach was used, with data collected through interviews, observations, and documentation involving key informants, such as the Head of BPBD Manado City. The data were processed using Miles et al.’s (2014) interactive analysis model, which includes data condensation, data display, and conclusion drawing. The findings reveal that BPBD plays three primary roles in disaster management. First, as a coordinator, BPBD acts as a command center, ensuring effective collaboration between government agencies, military (TNI), police, NGOs, and volunteers during disaster events. Second, as a regulator, BPBD formulates administrative and technical policies, including disaster management plans based on risk assessments and stakeholder-driven frameworks. Third, as an executor, BPBD directly implements activities in disaster management, including preparedness, emergency response, and post-disaster recovery, with an Incident Commander maintaining operational control during emergencies. Challenges faced by BPBD include low public discipline, limited awareness of disaster risks, inadequate equipment, and insufficient human resources in both quality and quantity. To address these issues, BPBD has initiated several efforts, including capacity building through training programs, promoting community-based disaster management, and establishing partnerships with national and international institutions such as UNDP and FAO. These efforts highlight the significance of an integrated, participatory, and coordinated disaster management system at the local government level. The study underscores the need for continued improvement in disaster management capabilities and community involvement.